Pain Symptoms in Optic Neuritis - Yang, Xiayin; Li, Xuefen; Lai, Mengying; Wang, Jincui; Tan, Shaoying; Chan, Henry Ho-lung (Frontiers in Pain Research, 2022)
Signs and symptoms of optic neuritis (ON), an autoimmune disorder of the central nervous system (CNS), differ between patients. Pain, which is commonly reported by ON patients, may be the major reason for some patients to visit the clinic. This article reviews the presence of pain related to ON with respect to underlying disorders, including multiple sclerosis (MS), neuromyelitis optica spectrum disorder (NMOSD), and myelin oligodendrocyte glycoprotein associated disease (MOGAD). The aim of this review is to provide an overview of pain symptoms in accordance with the context of various pathophysiological explanations, assist in differential diagnosis of ON patients, especially at the onset of disease, and make recommendations to aid physicians make decisions for follow up diagnostic examinations.